Penggunaan Quizizz Sebagai Media Pembelajaran Interaktif pada Pembelajaran Matematika - Erna Budi Setiawati; Syamsa Azilla; Afrasiska Felisita Alus; Aprillia Intan; Fhadila Riski Aryani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The development of technology in education has encouraged the use of more innovative and interactive learning media to improve the quality of mathematics learning. One of the most widely used media is Quizizz, a game-based learning platform that creates an engaging and enjoyable learning environment. This study aims to examine the use of Quizizz as an interactive learning medium in mathematics learning and to explain its benefits and potential in improving students' motivation, engagement, and learning outcomes. This study employed a qualitative descriptive approach using a literature review method. Data were obtained from various scientific sources, including journals, research articles, and books, and were analyzed using content analysis techniques. The findings indicate that the use of Quizizz in mathematics learning has a positive impact on students' motivation, learning interest, learning activities, and learning outcomes. Therefore, Quizizz can be used as an innovative alternative learning medium to create more interactive, engaging, and meaningful mathematics learning.